Organizational and economic mechanism to promote the effective employment of young people - Ye. A. Polishchuk, S. Yu. Tsokhla, (Opción, 2019)
The study is devoted to the improvement of organizational-economic mechanism to facilitate the process of effective youth employment with the aim of achieving sustainable socio-economic development in the region. Based on this survey significant imbalances were found that affect the efficiency of the process. The organizational and economic mechanism is improved. It ensures productive employment for young people and focuses on achieving efficiency, which determines the efficiency of the analyzed process on a number of parameters: economic processes in the labor market, educational processes, etc